2014
DOI: 10.5539/ijef.v6n2p75
|View full text |Cite
|
Sign up to set email alerts
|

Capital Flight to Savings Gap in Nigeria: An Assessment of the Socio-Economic Determinants

Abstract: Capital Flight has long been recognized as a problem for developing nations. Savings gap in some of these nations has widened over the years due to rising Capital Flight. This has limped domestic investment growth, employment creation and poverty alleviation. With these in view, this study seeks to underscore the socio-economic determinants of Capital Flight in Nigeria. Approaching the study, two measures of Capital Flight (hot money method and residual method) are modeled against a number of socio-economic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Theoretically, the determinants of capital flight have been discussed by portfolio adjustment theory and debt driven capital flight thesis, among others. The portfolio adjustment theory argued that capital flight occurs due to unstable macroeconomic and political environment in developing countries and the concurrent existence of better investment opportunities in advanced countries, like high foreign interest rates (Dim & Ezenekwe, 2014). According to the Debt Driven Capital Flight Thesis, heavy external debt of a country, is the main cause of capital flight (ibid).…”
Section: Determinants Of Capital Flightmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, the determinants of capital flight have been discussed by portfolio adjustment theory and debt driven capital flight thesis, among others. The portfolio adjustment theory argued that capital flight occurs due to unstable macroeconomic and political environment in developing countries and the concurrent existence of better investment opportunities in advanced countries, like high foreign interest rates (Dim & Ezenekwe, 2014). According to the Debt Driven Capital Flight Thesis, heavy external debt of a country, is the main cause of capital flight (ibid).…”
Section: Determinants Of Capital Flightmentioning
confidence: 99%
“…Capital flight is one of the debated topics in development and financial economics. While most of the debates have centered on how capital flight affects economic growth ( Cervena, 2006;Gusarova, 2009;Olawale & Ifedayo, 2016) , others have equally focused on what drives capital flight (Dim & Ezenekwe, 2014;Harrigan, Mavrotas, & Yusop, 2002;Raheem, 2015). Capital flight refers to part of domestic savings sent abroad.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The portfolio choice theory posits that capital flight occurs as a result of agent desires to optimize yields on capital for a given level of risk` (Collier et al, 2001). The theory also argues that, the occurrence of capital flight is due to the unstable macroeconomic and political environment in developing countries and the concurrent existence of better investment opportunities in advanced countries including high foreign interest rates (Dim and Ezenekwe, 2014). Thus, a rational profit maximizing agent will invest abroad if the risk adjusted returns are higher abroad than in the domestic economy.…”
Section: Introductionmentioning
confidence: 99%
“…A number of empirical studies have identified various factors responsible for outflows of capital in developing countries. These factors include exchange rate misalignment, interest rate differentials, fiscal deficit, increasing external debt, accelerating inflation, slowing economic growth rate, rising taxes, weak financial sector, political instability, weak property right and poor governance (Ajayi, 1995;Ali & Walters, 2011;Conesa, 1987;Dim & Ezenekwe, 2014;Fedderke & Liu, 2002;Harrigan et al, 2002;Lawanson, 2007;Le & Zak, 2006;Lensink, Hermes, & Murinde, 2000;Makochekanwa, 2007;Markowitz, 1952;Murinde, Hermes, & Lensink, 1996;Ndikumana & Boyce, 2003;Olopoenia, 2000;Onwioduokit, 2001;Raheem, 2015). In spite of the above factors, empirical studies have also produced mixed results for determinants of capital flight in developing countries ( Ali & Walter 2011;Ndikumana & Boyce, 2012;Ng"eno, 2000;Nyoni, 2000;Olopoenia, 2000;Onwioduokit, 2001;Pastor, 1990;Raheem, 2015).…”
Section: Introductionmentioning
confidence: 99%